The global mobility decisions of professional sailors' spouses. Issue 2 (12th June 2017) - Mutter, Joanne
Abstract : Purpose: The purpose of this paper is to identify the factors informing spousal global mobility decisions within the context of sporting expatriation. Findings contribute to the non-corporate global mobility literature as well as providing an empirical enhancement to the family relatedness of work decisions framework. Design/methodology/approach: In this qualitative study, in-depth interviews gave voice to 21 spouses of professional sailors who have experienced both trailing their spouse and staying behind. Findings: Access to empathetic social support, the potential impact on children, and the spouse's career were all found to influence the spouse's dynamic global mobility decision making. Research limitations/implications: The study is limited by the cross-sectional nature of the research. Future longitudinal research into the impact of spousal preferences would identify the on-going effect of their decision(s) to relocate or to stay behind. Practical implications: Providing organisations with an understanding of the familial issues their global talent may factor into their work mobility decisions will allow them to implement appropriate family-focussed support, irrespective of the choice to engage, or not engage, in global mobility. Originality/value: By grounding the study in the under-researched sporting arena, the author contributes to the emerging non-corporate expatriate conversation. Furthermore, the family relatedness of work-related decisions framework was found to provide a useful conceptual foundation for understanding decision making in an international context.